Gels handbook : fundamentals, properties and applications; VOL.2 - Demirci, Utkan; Ed. Khademhosseini, Ali; Ed (World Scientific, 2016)
Volume 1 covers state-of-art knowledge and techniques of fundamental aspects of hydrogel physics and chemistry with an eye on bioengineering applications.